A data fusion approach to optimize compositional stability of halide perovskites - Sun, Shijing; Tiihonen, Armi; Oviedo, Felipe; Liu, Zhe; Thapa, Janak; Zhao, Yicheng; Hartono, Noor Titan P.; Goyal, Anuj; Heumüller, Thomas; Batali, Clio; Encinas, Alex; Yoo, Jason J.; et al. (Matter, 2021)
Search for resource-efficient materials in vast compositional spaces is an outstanding challenge in creating environmentally stable perovskite semiconductors. We demonstrate a physics-constrained sequential learning framework to subsequently identify the most stable alloyed organic-inorganic perovskites. We fuse data from high-throughput degradation tests and first-principle calculations of phase thermodynamics into an end-to-end Bayesian optimization algorithm using probabilistic constraints. By sampling just 1.8% of the discretized CsxMAyFA1−x−yPbI3 (MA, methylammonium; FA, formamidinium) compositional space, perovskites centered at Cs0.17MA0.03FA0.80PbI3 show minimal optical change under increased temperature, moisture, and illumination with >17-fold stability improvement over MAPbI3. The thin films have 3-fold improved stability compared with state-of-the-art multi-halide Cs0.05(MA0.17FA0.83)0.95Pb(I0.83Br0.17)3, translating into enhanced solar cell stability without compromising conversion efficiency. Synchrotron-based X-ray scattering validates the suppression of chemical decomposition and minority phase formation achieved using fewer elements and a maximum of 8% MA. We anticipate that this data fusion approach can be extended to guide materials discovery for a wide range of multinary systems. Despite recent intensive efforts to improve the environmental stability of halide perovskite materials for energy harvesting and conversion, traditional trial-and-error explorations face bottlenecks in the navigation of vast chemical and compositional spaces. We develop a closed-loop optimization framework that seamlessly marries data from first-principle calculations and high-throughput experimentation into a single machine learning algorithm. This framework enables us to achieve rapid optimization of compositional stability for CsxMAyFA1−x−yPbI3 perovskites while taking the human out of the decision-making loop. We envision that this data fusion approach is generalizable to directly tackle challenges in designing multinary materials, and we hope that our successful showcase on perovskites will encourage researchers in other fields to incorporate knowledge of physics into the search algorithms, applying hybrid machine learning models to guide discovery of materials in high-dimensional spaces. Data fusion combines first-principle calculations and high-throughput experimentation into an end-to-end closed-loop optimization framework, allowing an accelerated search of alloyed halide perovskites in a combinatorial space without human intervention.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Bayesian optimization; data fusion; density-functional theory; energy materials; high-throughput experimentation; machine learning; MAP4: Demonstrate; perovskite stability

Cage Molecules Stabilize Lead Halide Perovskite Thin Films - Sun, Shijing; Liu, Ming; Thapa, Janak; Hartono, Noor Titan Putri; Zhao, Yicheng; He, Donglin; Wieghold, Sarah; Chua, Matthew; Wu, Yue; Bulović, Vladimir; Ling, Sanliang; Brabec, Christoph; et al. (Chemistry of Materials, 2022)
The environmental stability of hybrid organic-inorganic perovskite (HOIP) materials needs to increase to enable their widespread adoption in thin-film solar and optoelectronic devices. Molecular additives have recently emerged as an effective strategy for regulating HOIP crystal growth and passivating defects. However, to date the choice of additives is largely limited to a dozen or so materials under the design philosophy that high crystallinity is a prerequisite for stable HOIP thin films. In this study, we incorporate porous organic cages (POCs) as functional additives into perovskite thin films for the first time and investigate the HOIP-POC interaction via a combined experimental and computational approach. POCs are significantly larger than the small-molecule additives explored for HOIP synthesis to date but much smaller than polymeric sealants. Partially amorphized composites of MAPbI3 (methylammonium lead iodide, HOIP) and RCC3 (an amine POC) form a network-like surface topography and lead to an increase in the optical bandgap from 1.60 to 1.63 eV. Further in situ optical imaging suggests that RCC3 can delay the MAPbI3 film degradation onset up to 50× under heat and humidity stresses, showing promise for improving reliability in HOIP-based solar-cell and light-emitting applications. Furthermore, there is evidence of molecular interactions between RCC3 and MAPbI3, as fingerprinted by the suppressed N-H stretching mode in MA+ from Fourier transform infrared (FTIR) spectra and density functional theory (DFT) simulations that suggest strong hydrogen bonding between MA+ and RCC3. Given the diversity of POCs and HOIPs, our work opens a new avenue to stabilize HOIPs via tailored molecular interactions with functional organic materials.
CRIS-Team Scopus Importer:2022-11-11

Characterization of ADA-GEL Based Hydrogels Combined with Mesoporous Bioactive Glass Nanoparticles (MBGNs) and Human Platelet Lysate (HPL) for 3D (Bio)Printing - Zhao, Yicheng; Bider, Faina; Boccaccini, Aldo R. (Macromolecular Materials and Engineering, 2025)
With the emergence of 3D bioprinting, tissue repair strategies have become more sophisticated and multifunctional. Natural biomaterials like alginate and gelatin have been widely studied to formulate bioinks due to their excellent biocompatibility and biodegradable characteristics. However, the requirement for balanced features combining adjustable degradation rate, printability, and biological functionality is still hard to achieve. In this study, alginate dialdehyde (ADA) – gelatin (GEL) based hydrogels have been supplemented with mesoporous bioactive glass nanoparticles (MBGNs) and human platelet lysate (HPL) to enhance the biological performance. MBGNs can reduce the degradation of ADA-GEL 3D printed scaffolds and induce a mineralization effect while HPL is added as a source of growth factors. Improved printability and higher shape fidelity are observed by incorporating 0.1% (w/v) MBGNs, however, the addition of HPL led to a slight decrease in 3D printed shape fidelity. On the other hand, MBGNs and HPL both presented positive effects to improve cell activity and viability, which is characterized by using MC3T3-E1 pre-osteoblast cells. The ADA-GEL-based hydrogel with the incorporation of 0.1% (w/v) MBGNs and 5% (v/v) HPL shows the most balanced features, making it a promising biomaterial for 3D bioprinting of bone tissue scaffolds.
CRIS-Team Scopus Importer:2025-06-13
Keywords: 3D printing; bioactive glass nanoparticles; biofabrication; human platelet lysate; hydrogel

Discovery of temperature-induced stability reversal in perovskites using high-throughput robotic learning - Zhao, Yicheng; Hauch, Jens; Zhang, Jiyun; Xu, Zhengwei; Sun, Shijing; Langner, Stefan; Hartono, Noor Titan Putri; Heumüller, Thomas; Hou, Yi; Elia, Jack; Li, Ning; Matt, Gebhard; et al. (Nature Communications, 2021)
Stability of perovskite-based photovoltaics remains a topic requiring further attention. Cation engineering influences perovskite stability, with the present-day understanding of the impact of cations based on accelerated ageing tests at higher-than-operating temperatures (e.g. 140°C). By coupling high-throughput experimentation with machine learning, we discover a weak correlation between high/low-temperature stability with a stability-reversal behavior. At high ageing temperatures, increasing organic cation (e.g. methylammonium) or decreasing inorganic cation (e.g. cesium) in multi-cation perovskites has detrimental impact on photo/thermal-stability; but below 100°C, the impact is reversed. The underlying mechanism is revealed by calculating the kinetic activation energy in perovskite decomposition. We further identify that incorporating at least 10 mol.% MA and up to 5 mol.% Cs/Rb to maximize the device stability at device-operating temperature (<100°C). We close by demonstrating the methylammonium-containing perovskite solar cells showing negligible efficiency loss compared to its initial efficiency after 1800 hours of working under illumination at 30°C.
CRIS-Team Scopus Importer:2021-05-21

Efficient, stable, and fully printed carbon-electrode perovskite solar cells enabled by hole-transporting bilayers - Du, Tian; Qiu, Shudi; Zhou, Xin; Le Corre, Vincent Marc; Wu, Mingjian; Dong, Lirong; Peng, Zijian; Zhao, Yicheng; Jang, Dongju; Spiecker, Erdmann; Brabec, Christoph; Egelhaaf, Hans-Joachim (Joule, 2023)
Printable planar carbon electrodes emerge as a promising replacement for thermally evaporated metals as the rear contact for perovskite solar cells (PSCs). However, the power conversion efficiencies (PCEs) of the state-of-the-art carbon-electrode PSC (c-PSC) noticeably lag behind their metal-electrode counterparts. Here, we propose a hole-transporting bilayer (HTbL) configuration to improve the fill factor and the open-circuit voltage of c-PSCs simultaneously. The HTbL is prepared by sequentially blade coating two organic semiconductors between perovskite and carbon, with the outer HTL enhancing hole extraction to carbon, while the inner HTL mitigates perovskite surface recombination. Consequently, our fully printed c-PSCs with HTbL outperform those with single HTL, and a stabilized champion PCE of 19.2% is achieved compared with that of 17.3%. Our prototype c-PSC stably operates during 1 sun, 65°C aging test (ISOS-L-2I) for 2,500 h showing negligible PCE drop, validating its potential as a highly cost-effective photovoltaic technology.
CRIS-Team Scopus Importer:2023-08-18
Keywords: bilayer; carbon electrode; fully printed perovskite solar cells; hole transporting; stability

Exploring the Steric Hindrance of Alkylammonium Cations in the Structural Reconfiguration of Quasi-2D Perovskite Materials Using a High-throughput Experimental Platform - Zhang, Jiyun; Wu, Jianchang; Langner, Stefan; Zhao, Baolin; Xie, Zhiqiang; Hauch, Jens; Afify, Hany A.; Barabash, Anastasia; Luo, Junsheng; Sytnyk, Mykhailo; Meng, Wei; Zhang, Kaicheng; et al. (Advanced Functional Materials, 2022)
Reduced-dimensional (2D or quasi-2D) perovskites have recently attracted considerable interest due to their superior long-term stability. The nature of the intercalating cations plays a key role in determining the physicochemical properties and stability of the quasi-2D perovskites. Here, the thermal stability of a series of 2D Ruddlesden−Popper (RP) perovskites is studied using seven types of intercalating cations with increasing linear carbon-chain length from ethylammonium (EA) to n-dodecylammonium (DA) through a high-throughput platform. The results show that long-chain cations in quasi-2D perovskite films lead to strong steric hindrance between adjacent perovskite domains, thus suppressing Ostwald ripening during the thermal-aging process. For short-chain cations, increased-dimensional phase redistribution during the aging period is observed, which can benefit a concomitant regeneration of the 3D/3D-like perovskite phases. The impact of steric hindrance on structural reconfiguration and the subsequent phase redistribution in quasi-2D perovskites are systematically characterized by UV–vis absorption spectra, photoluminescence spectra, and X-ray diffraction patterns. Due to the steric hindrance effect, an optimal chain length is found to maximize film stability by balancing the water/oxygen resistance and increased-dimensional phase redistribution. This work provides new insight into the thermal stability of quasi-2D perovskites.
CRIS-Team Scopus Importer:2022-09-02
Keywords: 2D perovskite materials; high-throughput platform; stability performance; steric hindrance; steric structure and reconfiguration

Facet-Dependent Surface Trap States and Carrier Lifetimes of Silicon - Tan, Chih Shan; Zhao, Yicheng; Guo, Rong Hao; Chuang, Wei Tsung; Chen, Lih Juann; Huang, Michael H. (Nano Letters, 2020)
The facet-dependent electrical conductivity properties of silicon wafers result from significant band structure differences and variations in bond length, bond geometry, and frontier orbital electron distribution between the metal-like and semiconducting planes of silicon. To further understand the emergence of conductivity facet effects, electrochemical impedance measurements were conducted on intrinsic Si 100, 110, and 111 wafers. The attempt-to-escape frequency, obtained from temperature-dependent capacitance versus applied frequency curves, and other parameters derived from typical semiconductor property measurements were used to construct a diagram of the trap energy level (Et) and the amount of trap states Nt(Et). The trap states are located 0.61-0.72 eV above the silicon conduction band. Compared to 100 and 110 wafers, Si 111 wafer shows far less densities of trap states over the range of -0.2 to 2 V. Since these trap states inhibit direct electron excitation to the conduction band, the 111 wafer having much fewer trap states presents the best electrical conductivity property. Impedance data also provide facet-specific carrier lifetimes. The 111 surface gives consistently the lowest carrier lifetime, which reflects its high electrical conductivity. Lastly, ultraviolet photoelectron spectra and diffuse reflectance spectra were taken to obtain Schottky barriers between Ag and contacting Si wafers. The most conductive 111 surface presenting the largest Schottky barrier means the degrees of surface band bending used to explain facet-dependent electrical behaviors cannot be reliably attained this way.
CRIS-Team Scopus Importer:2020-03-10
Keywords: carrier lifetime; facet-dependent properties; impedance measurements; silicon; trap states

Integrated System Built for Small-Molecule Semiconductors via High-Throughput Approaches - Wu, Jianchang; Zhang, Jiyun; Hu, Manman; Reiser, Patrick; Torresi, Luca; Friederich, Pascal; Lahn, Leopold; Kasian, Olga; Guldi, Dirk Michael; Perez-Ojeda Rodriguez, Maria Eugenia; Barabash, Anastasia; Rocha Ortiz, Juan Sebastian; et al. (Journal of the American Chemical Society, 2023)
High-throughput synthesis of solution-processable structurally variable small-molecule semiconductors is both an opportunity and a challenge. A large number of diverse molecules provide a possibility for quick material discovery and machine learning based on experimental data. However, the diversity of the molecular structure leads to the complexity of molecular properties, such as solubility, polarity, and crystallinity, which poses great challenges to solution processing and purification. Here, we first report an integrated system for the high-throughput synthesis, purification, and characterization of molecules with a large variety. Based on the principle “Like dissolves like,” we combine theoretical calculations and a robotic platform to accelerate the purification of those molecules. With this platform, a material library containing 125 molecules and their optical-electronic properties was built within a timeframe of weeks. More importantly, the high repeatability of recrystallization we design is a reliable approach to further upgrading and industrial production.<br

Intercalating-Organic-Cation-Induced Stability Bowing in Quasi-2D Metal-Halide Perovskites - Zhang, Jiyun; Langner, Stefan; Wu, Jianchang; Kupfer, Christian; Lüer, Larry; Meng, Wei; Zhao, Baolin; Liu, Chao; Daum, Manuel; Osvet, Andres; Li, Ning; Halik, Marcus; et al. (ACS Energy Letters, 2022)
Quasi-2D metal-halide perovskites with Ruddlesden-Popper structures have shown promising stability due to the protective effects of the intercalating organic cations. However, a systematic study of the effect of intercalating organic cations on stability has rarely been reported. Here we use a high-throughput-robot platform to fabricate over 300 perovskite films and study the effect of cations and their concentrations on the thermal stability of perovskite films. We find that approximately 20-25 mol % of intercalating organic cations into MAPbI3 (nominal n = 4/5) can maximize the film stability, while higher/lower concentrations lead to inferior stability, which is termed stability bowing in analogy to band-gap bowing. A model with two competitive effects of the intercalating organic cation (better protection vs more defects) is proposed to rationalize this behavior. We anticipate this work to provide new insights into the stability of quasi-2D perovskites.
CRIS-Team Scopus Importer:2022-02-11

Inverse design workflow discovers hole-transport materials tailored for perovskite solar cells - Wu, Jianchang; Torresi, Luca; Hu, Manman; Reiser, Patrick; Zhang, Jiyun; Rocha-Ortiz, Juan S.; Wang, Luyao; Xie, Zhiqiang; Zhang, Kaicheng; Park, Byung-Wook; Barabash, Anastasia; Zhao, Yicheng; et al. (Science, 2024)
The inverse design of tailored organic molecules for specific optoelectronic devices of high complexity holds an enormous potential but has not yet been realized. Current models rely on large data sets that generally do not exist for specialized research fields. We demonstrate a closed-loop workflow that combines high-throughput synthesis of organic semiconductors to create large datasets and Bayesian optimization to discover new hole-transporting materials with tailored properties for solar cell applications. The predictive models were based on molecular descriptors that allowed us to link the structure of these materials to their performance. A series of high-performance molecules were identified from minimal suggestions and achieved up to 26.2% (certified 25.9%) power conversion efficiency in perovskite solar cell
CRIS-Team Scopus Importer:2025-02-04

Light intensity modulated impedance spectroscopy (LIMIS) in all-solid-state solar cells at open-circuit - Almora, Osbel; Zhao, Yicheng; Du, Xiaoyan; Heumüller, Thomas; Matt, Gebhard; Garcia-Belmonte, Germà; Brabec, Christoph (Nano Energy, 2020)
Potentiostatic impedance spectroscopy (IS) is a well-established characterization technique for elucidating the electric resistivity and capacitive features of materials and devices. For solar cells, by applying a small voltage perturbation the current signal is recorded and the recombination processes and defect distributions can be accessed. In this work, a photo-impedance approach, named “light intensity modulated impedance spectroscopy” (LIMIS), is first time tested in all-solid-state photovoltaics by individually recording photocurrent (IMPS) and photovoltage (IMVS) responsivity signals due to a small light perturbation at open-circuit (OC), and combining them: LIMIS = IMVS/IMPS. The experimental LIMIS spectra from silicon, organic, and perovskite solar cells are presented and compared with IS. Our theoretical analyses, including equivalent circuit models, show a correction to the lifetimes values by obtaining the total differential resistances and capacitances combining IS and LIMIS. This correction addresses some discrepancies among different techniques, as also shown with photo-induced transient photovoltage. The experimental differences between IS and LIMIS proves the unsuitability of the superposition principle and suggest a bias-dependent photo-current correction to the empirical Shockley equation of the steady-state current at different illumination intensities around OC. In addition, new features are reported for the low-frequency capacitance of perovskite solar cells.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Charge carrier generation rate; Impedance spectroscopy; Light intensity modulation; Perovskites; Photocurrent; Solar cells

Phase diagram and stability of mixed-cation lead iodide perovskites: A theory and experiment combined study - Xu, Zhengwei; Zhao, Yicheng; Zhang, Jiyun; Chen, Keqiu; Brabec, Christoph; Feng, Yexin (Physical Review Materials, 2020)
Alloying structurally similar perovskites to form mixed-cation lead iodide perovskites, e.g., Cs(x)FA((1-x))PbI(3), MA(x)FA((1-x))PbI(3), and Cs(x)MA(y)FA((1-x-y)) PbI3, could improve the performance of perovskite-based solar cells and light-emitting diodes. However, a phase diagram of them and a clear understanding of the underlying atomic-scale mechanism are still lacking. Using ab initio calculations combined with high-throughput experimentation, we demonstrate the phase diagram of mixed-cation lead iodide perovskites. Only a small proportion of monovalent cations (Cs+/Rb+/MA(+)) could be incorporated into the FAPbI(3)/MAPbI(3) matrix; otherwise it will be separated into delta-CsPbI3, delta-RbPbI3, MAI, etc. The smaller the radius of doping cations, the harder it is to incorporate them into a perovskite lattice and the easier it is to stabilize the perovskite phase. In FAPbI(3)-based multication perovskites, moreover, over 10 mol % alloying is needed to convert delta phase to alpha phase at room temperature. The combined upper and lower limits for doping concentration restrict the appropriate alloying ratio to a narrow window. We further plot the relative energy diagram for triple-cation perovskite Cs(x)MA(y)FA((1-x-y))PbI(3), which reveals the ideal doping ratio for uniform stable alloying. This theory-experiment-combined study provides a clear microscopic picture of phase stability and segregation for mixed-cation perovskite solids.
CRIS-Team WoS Importer:2020-10-09

Reducing Open-Circuit Voltage Losses in All-Inorganic Perovskite Cells by Dedoping - Peng, Zijian; Tian, Jingjing; Zhang, Kaicheng; These, Albert; Xie, Zhiqiang; Zhao, Yicheng; Osvet, Andres; Guo, Fei; Lüer, Larry; Li, Ning; Brabec, Christoph (ACS Energy Letters, 2023)
CsPbI2Br is an attractive photovoltaic material due to its promising optoelectronic properties. However, the corresponding perovskite solar cells (PSCs) with p-i-n configuration suffer from low open-circuit voltage (VOC) and fill factor (FF), limiting their application in tandem solar cells. Here, we propose using the fullerene ICBA as the electron charge transporting layer (ETL), forming a better interfacial contact and enhancing the internal quasi-Fermi level splitting (QFLS). A further reduction of VOC losses of around 0.1 V was achieved by an ultrathin phenethylammonium chloride (PEACl) layer between the perovskite and the ETL. We precisely study the VOC improvement and find that passivation of surface recombination contributes only 20 mV, while more importantly, a major increase of 80 mV is achieved by dedoping the perovskite surface, which removes a non-negligible electron extraction barrier. Our results give helpful direction regarding how to further improve VOC in p-i-n perovskite cells.
CRIS-Team Scopus Importer:2023-04-21

Revealing Degradation Mechanisms in 3D/2D Perovskite Solar Cells under Photothermal Accelerated Ageing - Peng, Zijian; Vincze, Andrej; Streller, Fabian; Le Corre, Vincent Marc; Zhang, Kaicheng; Li, Chaohui; Tian, Jingjing; Liu, Chao; Luo, Junsheng; Zhao, Yicheng; Späth, Andreas; Fink, Rainer; et al. (Energy and Environmental Science, 2024)
Three-dimensional/two-dimensional (3D/2D) heterojunctions in perovskite solar cells exhibit excellent optoelectronic properties and enhanced stability under mild ageing conditions. However, their performance degrades drastically under harsh ageing conditions. This study reveals the intrinsic instability of mono-ammonium based 2D perovskites (2D-mono) under photo-thermal ageing, which decompose into PbI2 and metallic lead (Pb0). The structural collapse promotes vacancy formation and facilitates iodide migration to the anode. As a result, it triggers a redox reaction that reduces the transport layer’s mobility and doping concentration, leading to a significant increase in series resistance. Compared to mono-ammonium-2D structure, di-ammonium-2D (2D-di) based interfaces demonstrate superior structural stability and effectively block iodide migration into the transporting layer. However, blocking-induced uneven iodide distribution leads to interstitial defect formation in the 3D layer, exacerbating non-radiative recombination. To address it, we propose a strategical method by incorporating 2D-di in the 3D bulk instead of on the top surface, which effectively confines mobile ions within the grain and suppresses cation phase segregation. This optimization yields stable perovskite solar cells with an extrapolated operational T80 lifetime exceeding 560 hours under harsh conditions (85°C and 2-sun illumination

Robot-Based High-Throughput Screening of Antisolvents for Lead Halide Perovskites - Gu, Ening; Tang, Xiaofeng; Langner, Stefan; Duchstein, Patrick; Zhao, Yicheng; Levchuk, Ievgen; Kalancha, Violetta; Stubhan, Tobias; Hauch, Jens; Egelhaaf, Hans-Joachim; Zahn, Dirk; Osvet, Andres; et al. (Joule, 2020)
Solution-based processing of photovoltaic materials has important advantages, including lower overall costs and easier upscaling of fabrication, where the solvents play an essential role. Antisolvent crystallization technique is often applied to achieve high-quality perovskite materials. However, the basic chemistry of the solvent-antisolvent crystallization is still not well understood. Besides, common antisolvents are toxic, and their number is limited. In this work, a novel robot-based method was used to screen the efficient antisolvents for different solvent-perovskite systems. 336 combinations of perovskite-solvent-antisolvent could be prepared and characterized by the integrated robotic platform in 2 days. In addition, we provided a detailed working mechanism of the solvent-antisolvent crystallization approach. Furthermore, hundreds of potential antisolvents were proposed based on high-throughput screening and simulation. Verification tests match well with theory, and all reported antisolvents used for photovoltaic device optimizations are within our predicted range of the Hansen space, indicating that the predictions are reliable. In terms of solution-processed lead halide perovskite optoelectrical materials, suitable antisolvent is essential for the crystallization and properties of final products. Conventional experiments of antisolvent selections are based on the manual time-consuming trial-error methods, which cannot meet today's increasing demands. In this work, a robot-based method was used to screen the antisolvents for different solvent-perovskite systems in a high-throughput manner to study the influence of interactions among the solvent molecules, cations, metal-halides, and antisolvents, to build an informative database, and to reveal the working mechanism and selection criteria of antisolvents. Besides, simulations based on the screening results provide hundreds of potential antisolvents. Corresponding verification tests evidenced that our predictions are reliable and vital for designing future efficient mixed solvent systems for the fabrication of perovskite optoelectrical materials. A robotic platform is adopted to conduct a comprehensive solvent engineering for making lead halide perovskites in a high-throughput manner. Deeper insights into the working mechanisms and selection criteria of antisolvents are investigated and summarized. In addition, a reliable antisolvent database is established, and verification tests match well with the theory. Furthermore, our work provides significant guidance for designing functional and environment-friendly mixed solvent systems to fabricate high-quality perovskite materials or devices.
CRIS-Team Scopus Importer:2020-08-21
Keywords: antisolvents; automated research; high-throughput method; lead halide complexes; lead halide perovskite; solvent engineering

SnO2-in-Polymer Matrix for High-Efficiency Perovskite Solar Cells with Improved Reproducibility and Stability - Wei, Jing; Guo, Fengwan; Wang, Xi; Xu, Kun; Lei, Ming; Liang, Yongqi; Zhao, Yicheng; Xu, Dongsheng (Advanced Materials, 2018)
Understanding interfacial loss and the ways to improving interfacial property is critical to fabricate highly efficient and reproducible perovskite solar cells (PSCs). In SnO2-based PSCs, nonradiative recombination sites at the SnO2-perovskite interface lead to a large potential loss and performance variation in the resulting photovoltaic devices. Here, a novel SnO2-in-polymer matrix (i.e., polyethylene glycol) is devised as the electron transporting layer to improve the film quality of the SnO2 electron transporting layer. The SnO2-in-polymer matrix is fabricated through spin-coating a polymer-incorporated SnO2 colloidal ink. The polymer is uniformly dispersed in SnO2 colloidal ink and promotes the nanoparticle disaggregation in the ink. Owing to polymer incorporation, the compactness and wetting property of SnO2 layer is significantly ameliorated. Finally, photovoltaic devices based on Cs(0.05)FA(0.81)MA(0.14)PbI(2.55)Br(0.45) perovskite sandwiched between SnO2 and Spiro-OMeTAD layer are fabricated. Compared with the averaging power conversion efficiency of 16.2% with 1.2% deviation for control devices, the optimized devices exhibit an improved averaging efficiency of 19.5% with 0.25% deviation. The conception of polymer incorporation in the electron transporting layer paves a way to further increase the performance of planar perovskite solar cells.
Keywords: perovskite solar cells; reproducibility; SnO2-in-polymer matrix; stability

Solution-Growth Liquid-Phase Epitaxy of CsPbBr3 on NaCl by Optimizing the Substrate Dissolution - Elia, Jack; Levchuk, Ievgen; Hou, Yi; Matt, Gebhard; These, Albert; Zhao, Yicheng; Zhang, Jiyun; Forberich, Karen; Osvet, Andres; Götz, Klaus; Prihoda, Annemarie; Wu, Mingjian; et al. (Journal of Physical Chemistry C, 2023)
Since the earliest days of liquid-phase epitaxy (LPE) research, substrate stability has been a prerequisite for investigating nucleation and epitaxial growth. For flux- and melt-growth LPE, soluble substrates have always been viewed as problematic and difficult. However, solution-growth LPE transforms this disadvantage into a benefit by facilitating the creation of graded interfaces. In this study, we investigated the nucleation and growth of solution-grown LPE in the evaporation mode of soluble CsPbBr3 on freshly cleaved NaCl single-crystal substrates. Only two of the four main types of CsPbBr3 crystallization observed are epitaxial. The microscopic observation of composition gradients at the interface of CsPbBr3 grains and substrates reveals a promising opportunity to manipulate the lattice constant at the interface by simply controlling the temperature and concentration.
CRIS-Team Scopus Importer:2023-12-08

Spontaneously Self-Assembly of a 2D/3D Heterostructure Enhances the Efficiency and Stability in Printed Perovskite Solar Cells - Hu, Jinlong; Wang, Chuan; Qiu, Shudi; Zhao, Yicheng; Gu, Ening; Zeng, Linxiang; Yang, Yuzhao; Li, Chaohui; Liu, Xianhu; Forberich, Karen; Brabec, Christoph; Nazeeruddin, Mohammad Khaja; et al. (Advanced Energy Materials, 2020)
As perovskite solar cells (PSCs) are highly efficient, demonstration of high-performance printed devices becomes important. 2D/3D heterostructures have recently emerged as an attractive way to relieving the film inhomogeneity and instability in perovskite devices. In this work, a 2D/3D ensemble with 2D perovskites self-assembled atop 3D methylammonium lead triiodide (MAPbI3) via a one-step printing process is shown. A clean and flat interface is observed in the 2D/3D bilayer heterostructure for the first time. The 2D perovskite capping layer significantly suppresses nonradiative charge recombination, resulting in a marked increase in open-circuit voltage (VOC) of the devices by up to 100 mV. An ultrahigh VOC of 1.20 V is achieved for MAPbI3 PSCs, corresponding to 91% of the Shockley–Queisser limit. Moreover, notable enhancement in light, thermal, and moisture stability is obtained as a result of the protective barrier of the 2D perovskites. These results suggest a viable approach for scalable fabrication of highly efficient perovskite solar cells with enhanced environmental stability.
CRIS-Team Scopus Importer:2020-03-27
Keywords: 2D/3D heterojunctions; high efficiency; perovskite solar cells; self-assembly; stability

Steric Engineering Enables Efficient and Photostable Wide-Bandgap Perovskites for All-Perovskite Tandem Solar Cells - Wen, Jin; Zhao, Yicheng; Liu, Zhou; Gao, Han; Lin, Renxing; Wan, Sushu; Ji, Chenglong; Xiao, Ke; Gao, Yuan; Tian, Yuxi; Xie, Jin; Brabec, Christoph; et al. (Advanced Materials, 2022)
Wide-bandgap (WBG, ≈1.8 eV) perovskite is a crucial component to pair with narrow-bandgap perovskite in low-cost monolithic all-perovskite tandem solar cells. However, the stability and efficiency of WBG perovskite solar cells (PSCs) are constrained by the light-induced halide segregation and by the large photovoltage deficit. Here, a steric engineering to obtain high-quality and photostable WBG perovskites (≈1.8 eV) suitable for all-perovskite tandems is reported. By alloying dimethylammonium and chloride into the mixed-cation mixed-halide perovskites, wide bandgaps are obtained with much lower bromide contents while the lattice strain and trap densities are simultaneously minimized. The WBG PSCs exhibit considerably improved performance and photostability, retaining >90% of their initial efficiencies after 1000 h of operation at maximum power point. With the triple-cation/triple-halide WBG perovskites enabled by steric engineering, a stabilized power conversion efficiency of 26.0% in all-perovskite tandem solar cells is further obtained. The strategy provides an avenue to fabricate efficient and stable WBG subcells for multijunction photovoltaic devices.
CRIS-Team Scopus Importer:2022-06-03
Keywords: all-perovskite tandem solar cells; lattice strain; light-induced halide segregation; steric engineering; wide-bandgap perovskite solar cells

Strain-activated light-induced halide segregation in mixed-halide perovskite solids - Zhao, Yicheng; Miao, Peng; Elia, Jack; Hu, Huiying; Wang, Xiaoxia; Heumüller, Thomas; Hou, Yi; Matt, Gebhard; Osvet, Andres; Chen, Yu-Ting; Tarragó, Mariona; de Ligny, Dominique; et al. (Nature Communications, 2020)
Light-induced halide segregation limits the bandgap tunability of mixed-halide perovskites for tandem photovoltaics. Here we report that light-induced halide segregation is strain-activated in MAPb(I1−xBrx)3 with Br concentration below approximately 50%, while it is intrinsic for Br concentration over approximately 50%. Free-standing single crystals of CH3NH3Pb(I0.65Br0.35)3 (35%Br) do not show halide segregation until uniaxial pressure is applied. Besides, 35%Br single crystals grown on lattice-mismatched substrates (e.g. single-crystal CaF2) show inhomogeneous segregation due to heterogenous strain distribution. Through scanning probe microscopy, the above findings are successfully translated to polycrystalline thin films. For 35%Br thin films, halide segregation selectively occurs at grain boundaries due to localized strain at the boundaries; yet for 65%Br films, halide segregation occurs in the whole layer. We close by demonstrating that only the strain-activated halide segregation (35%Br/45%Br thin films) could be suppressed if the strain is properly released via additives (e.g. KI) or ideal substrates (e.g. SiO2).<br

Understanding the Limitations of Charge Transporting Layers in Mixed Lead–Tin Halide Perovskite Solar Cells - Zhang, Kaicheng; Forberich, Karen; Lüer, Larry; García Cerrillo, José; Meng, Wei; Du, Xiaoyan; Le Corre, Vincent Marc; Zhao, Yicheng; Niu, Tianqi; Xue, Qifan; Koster, L Jan Anton; Li, Ning; et al. (Advanced Energy and Sustainability Research, 2021)

Utilizing the unique charge extraction properties of antimony tin oxide nanoparticles for efficient and stable organic photovoltaics - Liu, Chao; Félix, Roberto; Forberich, Karen; Du, Xiaoyan; Heumüller, Thomas; Matt, Gebhard; Gu, Ening; Wortmann, Jonas; Zhao, Yicheng; Cao, Yuanyuan; He, Yakun; Ying, Lei; et al. (Nano Energy, 2021)
Simultaneously enhancing device performance and longevity, as well as balancing the requirements on cost, scalability, and simplification of processing, is the goal of interface engineering of organic solar cells (OSCs). In our work, we strategically introduce antimony (Sb3+) cations into an efficient and generic n-type SnO2 nanoparticles (NPs) host during the scalable flame spray pyrolysis synthesis. Accordingly, a significant switch of conduction property from an n-type character to a p-type character is observed, with a corresponding shift in the work function (WF) from 4.01 ± 0.02 eV for pristine SnO2 NPs to 5.28 ± 0.02 eV for SnO2 NPs with 20 mol. % Sb content (ATO). Both pristine SnO2 and ATO NPs with fine-tuned optoelectronic properties exhibit remarkable charge carrier extraction properties, excellent UV resistance and photo-stability being compatible with various state-of-the-art OSCs systems. The reliable and scalable pristine SnO2 and ATO NPs processed by doctor-blading in air demand no complex post-treatment. Our work offers a simple but unique approach to accelerate the development of advanced interfacial materials, which could circumvent the major existing interfacial problems in solution-processed OSCs.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Antimony doped tin oxide; Doping mechanism; Interface engineering; Metal oxide nanoparticles; Organic photovoltaics

UV-Inert ZnTiO3 Electron Selective Layer for Photostable Perovskite Solar Cells - Wei, Jing; Guo, Fengwan; Liu, Bing; Sun, Xiangyu; Wang, Xi; Yang, Zijiang; Xu, Kun; Lei, Ming; Zhao, Yicheng; Xu, Dongsheng (Advanced Energy Materials, 2019)
Although planar-structured perovskite solar cells (PSCs) have power conversion efficiencies exceeding 24%, the poor photostability, especially with ultraviolet irradiance (UV) severely limits commercial application. The most commonly-used TiO2 electron selective layer has a strong photocatalytic effect on perovskite/TiO2 interface when TiO2 is excited by UV light. Here a UV-inert ZnTiO3 is reported as the electron selective layer in planar PSCs. ZnTiO3 is a perovskite-structured semiconductor with excellent chemical stability and poor photocatalysis. Solar cells are fabricated with a structure of indium doped tin oxide (ITO)/ZnTiO3/Cs(0.05)FA(0.81)MA(0.14)PbI(2.55)Br(0.45)/Sprio-MeOTAD/Au. The champion device exhibits a stabilized power conversion efficiency of 19.8% with improved photostability. The device holds 90% of its initial efficiency after 100 h of UV soaking (365 nm, 8 mW cm(-2)), compared with 55% for TiO2-based devices. This work provides a new class of electron selective materials with excellent UV stability in perovskite solar cell applications.
CRIS-Team WoS Importer:2019-10-04

Visualizing and Suppressing Nonradiative Losses in High Open-Circuit Voltage n-i-p-Type CsPbI3 Perovskite Solar Cells - Meng, Wei; Hou, Yi; Karl, André; Gu, Ening; Tang, Xiaofeng; Osvet, Andres; Zhang, Kaicheng; Zhao, Yicheng; Du, Xiaoyan; García Cerrillo, José; Li, Ning; Brabec, Christoph (ACS Energy Letters, 2020)
Cesium lead iodide (CsPbI3) has attracted increasing attention for its photovoltaic applications, owing to its thermal stability and suitable band gap for tandem solar cells. However, the severe nonradiative recombination losses in CsPbI3-based perovskite solar cells generally restrict their open-circuit voltage (VOC) to the range of 0.9 to 1.1 V. This work uniquely reports a method to visualize all defect-assisted recombination pathways with photoluminescence (PL) techniques. Visible and valuable insight into the reduction of defect densities on a micrometer scale was obtained by the bottom surface and bulk passivation with barium hydroxide and trioctylphosphine oxide. The dual effects successfully improve the VOC of the solar cell from 0.87 to 1.17 V. These results highlight the potential of hyperspectral PL imaging as a powerful tool to give guidance to further suppress the nonradiative VOC losses in all-inorganic perovskites.
CRIS-Team Scopus Importer:2020-01-21